Pembelajaran Pola Gerak Tari Mutei Kawe pada Kegiatan Ekstrakurikuler di SMP N 2 Tebing Tinggi - Bunga Tri Irawan; Treny Hera; Fadhilah Hidayatullah (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research aims to describe the learning of Mutei Kawe dance movement patterns in extracurricular activities at SMP Negeri 2 Tebing Tinggi. This research uses qualitative research methods which can be interpreted as philosophical research methods used to study certain populations or samples, collect data using research instruments and analyze qualitative/statistical data. The results of the research show that 1). The teacher's preparation before carrying out extracurricular activities was very good, before learning started the teacher instructed students to immediately change into practical clothes and form neat and orderly lines. 2). The learning process for extracurricular dance activities at SMP Negeri 2 Tebing Tinggi is in the good category. Learning is carried out in 3 stages of activities, namely learning the initial movements, core movements and final movements and students are able to dance the Mutei Kawe dance. 3). And the extracurricular evaluation of the Mutei Kawe dance art used is a practical test by practicing the Mutei Kawe dance in groups in the form of individual assessments. month, namely 4-5x meetings.